International Aid and Urban Change Humanitarian Presence in Bamako, Abidjan, Nairobi and Juba - de Roulet, Pablo (Peter Lang International Academic Publishers, 2022)
The presence of expatriate humanitarian workers in African cities is not neutral. Country capitals receive large and sudden influx of expatriates during humanitarian crises responses. This book examines the influence of this presence on the local urban ecosystem, from the building of a security discourse to the self-segregation of aid agencies in expatriate enclaves. The examples of Abidjan, Bamako, Juba and Nairobi illustrate different variants of urban change induced by the normative power of aid organisations.